PENGELOLAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) ASTRA INTERNATIONAL 'NURANI ASTRA' DI MASA PANDEMI COVID-19 - Irwindy Sakinah Ariestanty (2021)
During the COVID-19 pandemic, companies that do corporate social responsibility (CSR) activities will adapt more, especially in their activities to help more in overcoming COVID-19 in Indonesia. One of the companies that active and participates in the response to COVID-19 in Indonesia through its CSR activities is PT Astra International Tbk. Through the CSR program 'Nurani Astra', Astra continues to assist the goverment and their stakeholders. Managing CSR during a pandemic will be different from managing CSR in previous times (the period before the pandemic comes). The purpose of this research is to find out how the management of Astra International's 'Nurani Astra' corporate social responsibility (CSR) program during the COVID-19 pandemic, to find out who are the stakeholders involved and what's their role in the 'Nurani Astra' CSR activity. This research uses descriptive qualitative method. The sources obtained in this study are through interviews and literature studies. The theory used in this research is stakeholder theory. The results of this study found that in the management of CSR 'Nurani Astra' during the COVID-19 pandemic, there are four stages: problem identification, planning, program implementation, and evaluation. Of course there are differences and challenges in the management of CSR during the COVID-19 pandemic, but these challenges are not considered a big enough challenge, because Astra can adapt to new situations. In addition, there are stakeholders who participate in this 'Nurani Astra' CSR activity, there are employees, the government, health agencies, and the community. They each have an important role in helping the sustainability of this 'Nura Astra' CSR activity.